Personalised regional modelling predicts tau progression in the human brain - Chaggar, Pavanjit; Vogel, Jacob; Binette, Alexa Pichet; Thompson, Travis B.; Strandberg, Olof; Mattsson-Carlgren, Niklas ; 0000-0002-8885-7724; Karlsson, Linda ; 0000-0002-0630-772X; Stomrud, Erik ; 0000-0002-0841-5580; Jbabdi, Saad; Magon, Stefano; Klein, Gregory; Hansson, Oskar ; 0000-0001-8467-7286; et al. (PLoS Biology, 2025)
Aggregation of the hyperphosphorylated tau protein is a central driver of Alzheimer’s disease, and its accumulation exhibits a rich spatiotemporal pattern that unfolds during the course of the disease, sequentially progressing through the brain across axonal connections. It is unclear how this spatiotemporal process is orchestrated, namely, to what extent the spread of pathologic tau is governed by transport between brain regions, local production, or both. To address this, we develop a mechanistic model from tau PET data to describe tau dynamics along the Alzheimer’s disease timeline. Our analysis reveals longitudinal changes in production and transport dynamics in two independent cohorts, with subjects in the early stage of the disease exhibiting transport-dominated spread, consistent with an initial spread of pathological tau seeds, and subjects in the late stage disease characterized primarily by local tau production. Further, we demonstrate that the model can predict accurately subject-specific longitudinal tau accumulation at the regional level, potentially providing a new clinical tool to monitor and classify patient disease progression.
Publisher Copyright: © 2025 Chaggar et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.